Model Pembuktian dalam Putusan Kabul Mahkamah Konstitusi: Studi Kasus Sengketa Pemilu Legislatif No. 86-03 26/PHPU.DPR.DPRD/XVII/2019 - Sari, Jingga Dian Eka Rindra; Maula, Rizal (Jurnal Konstitusi & Demokrasi, 2023)
This study aims to analyze the evidentiary model and legal implications of the Constitutional Court Decision Number 86-03-26/PHPU.DPR.DPRD/XVII/2019 related to the Legislative General Election dispute. Using the normative juridical method, this research examines the Court's reasoning in deciding the case and the legal consequences of the decision. This research also pays attention to the conformity between documents and testimonies of witnesses and experts submitted in the trial, as well as the integrity of voter data. The Constitutional Court encouraged the KPU to ensure the accuracy and validity of voter data to reduce potential disputes in the future. The verdicts affecting the implementation of re-voting in certain polling stations and the annulment of KPU decisions in some areas, demonstrating the importance of a fair and transparent evidentiary process in upholding justice. This research provides insight into how the Constitutional Court handles electoral disputes by affirming the fairness, integrity and legitimacy of the democratic process in Indonesia.